Management control systems on managing employees and its effect on performance in services sector / Maziana Zakaria - Zakaria, Maziana (2016)
Management control systems (MCS) were regarded as a helpful tool for organization in terms of controlling employees due to its nature dealing with resources and capabilities. Employees, currently, have become the central part in sustaining competitive advantage which has been argued that have a significant impact on performance. Employers are constantly searching for more relevant approaches in managing employees to achieve utmost performance, whilst employees are keen to enhance the benefits at work such as opportunities for more absorbing and inspiring work patterns. Therefore, the main objective of this study was to examine the nature of employees control as the elements of MCS on performance and the influence of task environment on MCS in services sector. Further consideration of wellbeing will take place as moderator in the relationship of MCS and performance. As such, this model eventually leads to having better on-going decision making. The employees control was incorporated in general MCS (omcs), interactive control (mics) and enabling control (mecs) systems as the elements of MCS. A questionnaire survey was conducted among managers in services organization which located in Peninsular Malaysia. An analysis of 166 survey responses shows mixed results for the hypotheses developed which empirically tested using Partial Least Square-SEM. For direct relationship, the results revealed that there is significant positive relationship between task environment and MCS. Mics and mecs were positively associated with non-financial performance; however, both insignificant on financial performance. The relationship between omcs and performance were found insignificant as expected. Findings also confirmed the moderating effect of the wellbeing in the relationship of omcs and non-financial performance. The moderating effect, conversely, was not established between mics and mecs on performance as well as omcs on financial performance. This study offers a significant contribution to the existing body of knowledge in MCS by expanding the theories (contingency and resource-based) via new elements, particularly, employees control and wellbeing. It was also shown that, an understanding of the antecedents of task environment in adopting MCS, notably, mics and mecs on non-financial performance in order to promote and support sounds employees' control. The moderating effect of wellbeing highlights preliminary evidence on the elements of employees control in MCS which focus on how to manage employees' documents and regulations for establishing commencement of MCS. Thus, enable managers to simultaneously exploit and explore richer management control information. However, this study also recognizes that the research limitations might diminish the generalization; particularly the number of sample and did not consider all the sectors other than services.